Development of Innovations in Retail Trade as A Response to Latest Trends in Consumption – Polish Perspective - Beata REFORMAT (Communications of International Proceedings, 2022)
The considerations presented in the article refer to an important strategic problem, which is innovation in retail trade. Their development in the market depends to a large extent on the needs and behavior of consumers, and new trends in consumption, which is fostered the development of  information and communication technologies. These phenomena determine the scope of the article, in which assumes the implementation of the following goals: 1) identification of new phenomenon and trends that occur in retail trade and consumer behavior, on which the nature and type of introduced innovations depends; 2) indication of innovation relationships in retail trade with the new trends in consumption; 3) analysis of selected examples of innovations introduced by retail trade entities in Poland in different areas of their market activity. The basic research methodology is the critical analysis of the literature and the case study method. Results of analyses allow to state that a considerable number of innovations in retail trade is a response to latest trends in consumption. They mainly consist in modification of store formats, introduction of new forms of trade, application of mobile technologies and implementation of changes in the sphere of marketing instruments associated with impact on target market.
Keywords: trends of consumption; retail trade; innovation